2014
DOI: 10.1002/mpr.1441
|View full text |Cite
|
Sign up to set email alerts
|

The ZInEP Epidemiology Survey: background, design and methods

Abstract: This article introduces the design, sampling, field procedures and instruments used in the ZInEP Epidemiology Survey. This survey is one of six ZInEP projects (Zürcher Impulsprogramm zur nachhaltigen Entwicklung der Psychiatrie, i.e. the "Zurich Program for Sustainable Development of Mental Health Services"). It parallels the longitudinal Zurich Study with a sample comparable in age and gender, and with similar methodology, including identical instruments. Thus, it is aimed at assessing the change of prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 80 publications
0
25
0
Order By: Relevance
“…Additional weights were introduced to account for nonresponse/ underrepresentation according to urbanicity status, education level, and the weight of any specific sex-birth year subgroup within the population of the 20-40 years old. The sampling and weighting procedures were described in detail by Ajdacic-Gross et al [2]. Additional analysis pooling all available individual data was performed in order to enlarge the statistical power of the findings derived from the three separate data sets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional weights were introduced to account for nonresponse/ underrepresentation according to urbanicity status, education level, and the weight of any specific sex-birth year subgroup within the population of the 20-40 years old. The sampling and weighting procedures were described in detail by Ajdacic-Gross et al [2]. Additional analysis pooling all available individual data was performed in order to enlarge the statistical power of the findings derived from the three separate data sets.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this discrepancy is probably a result of the instrument rather than explainable by factors such as regional differences between the PsyCoLaus sample and the Zurich Study and ZInEP sample, respectively. In contrast, the Zurich Study and the ZInEP study were parallelized with regard to basic methodological features (for more details see Ajdacic-Gross et al [2]) and showed more similarities. Second, while the basic findings distinguishing between PCS and the MOCS were consistent, the more detailed results depicted a relatively high degree of heterogeneity across the studies.…”
Section: Limitationsmentioning
confidence: 96%
See 1 more Smart Citation
“…In the final step, 227 subjects from the two subsamples were randomly selected for laboratory testing and longitudinal surveys based on their prior consent to undergo additional testing (see Ajdacic-Gross et al, 2014). Those initially assigned to the psychosis subsample additionally completed the PD questionnaires and vice versa.…”
Section: Study Design and Samplingmentioning
confidence: 99%
“…Thus participants were randomly assigned to either subgroup, which is why they did not differ in any characteristics besides the different questionnaires that they had to complete. A detailed rationale and description of the sampling procedure has been provided by Ajdacic-Gross et al (2014).…”
Section: Study Design and Samplingmentioning
confidence: 99%